My Science Book of Energy - Ardley, Neil, 1937-2004; King, Dave (Dorling Kindersley, 1992)
Finding out about science becomes fun with this exciting practical activity book. Packed with projects and simple experiments that can be carried out at home, it introduces the basic principles of science. All the experiments are easy to follow, with clear photographic step-by-step instructions.